152P Replicative potency of oncolytic VSV-GP differentially shapes the immune signature in three distinct syngeneic tumour models. (15th December 2019) - Wollmann, G; Spiesschaert, B; Das, K; Schreiber, L-M; Erlmann, P; Stierstorfer, B; von Laer, D; Mueller, P; Urbiola, C
Abstract: Background: Oncolytic viruses (OV) induce potent antitumor treatment effects not only via direct tumour infection and lysis but also via activation of innate and adaptive immune responses. As such, they show strong synergism in combination with various immunotherapy strategies. Here we address the question to what extend intratumoral viral replication of the vesicular stomatitis virus variant VSV-GP affects the tumour microenvironment of three different syngeneic mouse tumour models B16, TRAMP and LLC. Methods: To model tumours with higher permissivity for OVs we generated interferon receptor deficient cells (TRAMP-IFNAR1 -/- and LLC1-IFNAR1 -/- ). Bio-luminescent imaging was used to assess intratumoral virus propagation. Efficacy of VSV-GP was assessed in vivo in syngeneic C57BL/6 mice. The tumour micro environment was studied using flow cytometry, histology, multiplex cytokine ELISA and NanoString ® transcriptome analysis. Results: Intratumoral viral propagation was enhanced in the IFNAR1 -/- tumours compared to B16. In LLC1-IFNAR1 -/- tumours, VSV-GP treatment resulted in significant upregulation of over 300 immune-related genes, increase in tumour infiltrating lymphocytes and expression of pro-inflammatory cytokines. In contrast, immune activation markers in virus replication-restricted B16 tumours were only slightly increased. Yet, based on transcriptional analysis, we found a common VSV-GP treatment-associated immune gene signature. Furthermore, we have observed that VSV-GP induces an up-regulation of inflammatory cytokines in all tumour models, such as type-I IFN, IFN-γ and TNF-α, which correlates with an increase of the T-cell infiltration in the tumour. Other cytokines, such as IL-6 or IL-10, were found to be differently regulated depending on the model. Conclusion: In conclusion, we present a number of immune-activating consequences of virotherapy treatment in syngeneic tumour models with varying degree of virus propagation. Higher virus activity in the tumour qualitatively and quantitatively shapes the tumour microenvironment differently compared to tumours with restricted virus activity. Legal entity responsible for the study: The authors. Funding: Christian Doppler Research Association. Disclosure: G. Wollmann: Advisory / Consultancy, Research grant / Funding (self): Boehringer Ingelheim. B. Spiesschaert: Full / Part-time employment: Boehringer Ingelheim. P. Erlmann: Full / Part-time employment: Boehringer Ingelheim. B. Stierstorfer: Full / Part-time employment: Boehringer Ingelheim. D. von Laer: Advisory / Consultancy: Boehringer Ingelheim; Shareholder / Stockholder / Stock options, Licensing / Royalties: ViraTherapeutics. P. Mueller: Full / Part-time employment: Boehringer Ingelheim. All other authors have declared no conflicts of interest.